Peningkatan mutu lembaga pendidikan melalui kepemimpinan yang visioner - Arroichan, Muhammad Fatih; Sholihah, Khusna Nur Lailatus (Maliki Interdisciplinary Journal, 2023)
This research aims to explore the concept and role of visionary leadership in improving the quality of educational institutions. We will analyze case studies, empirical research, and other evidence to support the link between visionary leadership and improving education quality. This research is expected to provide valuable insights for education practitioners, policy makers, and researchers about the importance of visionary leadership in achieving better quality education and relevant to future needs. Improving the quality of educational institutions is a must to face the challenges of an increasingly complex era. In this context, visionary leadership plays a key role in bringing about positive change. Through strong vision, innovation, effective communication, and adaptability, visionary leadership has the potential to bring about positive changes in the quality of education.